FENOMENA TINGGINYA KONSUMSI KELAS MENENGAH PADA SISTEM PINJAMAN ONLINE BERKEDOK HUTANG DAHULU BAYAR BELAKANGAN - Benyta Putri Bahadiani; Junita Ruth Roselyne Hutagalung (Saskara : Indonesian Journal of Society Studies, 2022)
The existence of an online shopping platform proof of technological development. Shopee as the largest Marketplace in Indonesia provides the Shopee Paylater payment method, a method that provides credit to users. Shopee Paylater is one of the preferred payment methods because of the ease of providing loan funds for its users. Because it is easy for many users to buy goods because of spontaneity without first doing what will happen after making the purchase, giving rise to an impulsive buying attitude. This study focuses on the objectives of students using Paylater as a payment method and consumptive behavior among UNJ sociology students by using the theory of habitus according to Pierre Bourdieu. The results show that students use Shopee Paylater because the discounts offered are so many that students don't want these discounts to just end up giving birth to consumptive behavior and giving birth to impulsiveness. Furthermore, Shopee Paylater makes it easy for students to shop when they don't have money. However, it creates an attitude of waste and impulsiveness.